Effect of liquidity management on the profitability of Agrani Bank Limited and prospects of ABL’s SME products in future - Ahmed, Nazir (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.